"Change within Continuity": Sacred and Holy Spaces and Socialization in Bocha, Zimbabwe, ca. 1910–1960s. Issue 1 (2nd January 2022) - Magaya, Aldrin Tinashe
ABSTRACT: The article examines how a rural community in Bocha, Zimbabwe, molded Christianity to suit and serve its local everyday realities. It highlights the coexistence and interdependence between Christianity and the long-standing Bocha people's traditions. It contends that although ordinary churchgoers internalized Christian idioms and teachings, they did not give up being the Bocha. In doing so, it highlights how existing ways of socialization, social facts, local beliefs, spiritual needs, and customs shaped the understandings of sacred indigenous and Christian spaces. It argues that an existing pre-Christian tenet of tolerance created the right social environment for religious diversity and the coexistence of indigenous and Christian practices and beliefs. Thus, the article points to the persistence of pre-Christian culture within an increasingly Bocha Christian community in the first half of the twentieth century.